Contextualized 7Taps Microlearning Modules for Enhancing Metacognitive Skills of Grade 11 Students - Gabelo, Raymundo Jr. R. (Researchparks Publishing, 2025)
In recent years, educational institutions had increasingly adopted various technological tools to facilitate learning, improve engagement, and promote self-directed learning. This study contributed valuable insights into how the Grade 11 students' metacognitive skills can be enhanced to improve their educational outcomes. Specifically, utilizing contextualized 7taps Microlearning Modules in Practical Research 1 subject. This quantitative quasi- experimental study focused primarily on investigating the utilization of contextualized 7taps microlearning modules to enhance the metacognitive skills of grade 11 students at Bigaa Integrated National High School. The participants were 30 learners from 11- TVL, specifically 15 students from the HE strand and 15 students from the ICT strand. These learners utilized the tablets provided by the school and the local government of Cabuyao City. Both the control and experimental groups initially showed